Staff facing criminal proceedings: some considerations - Faruqi, Shad Saleem (Pejabat Penasihat Undang-Undang, 2015)
This article discusses situations where university staff face allegations of criminal conduct. Complaints may originate from outsiders, students, or fellow staff members. The police investigate the accusations, and depending on their findings, the case may be closed or the staff member may be charged in court. The article highlights considerations for handling such cases within the university context.